Effects of Olive Leaf Extracts as Natural Preservative on Retailed Poultry Meat Quality - Saleh, Ebeed; Morshdy, Alaa Eldin; El-Manakhly, Eman; Al-Rashed, Sarah; F. Hetta, Helal; Jeandet, Philippe; Yahia, Ramadan; El-Saber Batiha, Gaber; Ali, Eman (Foods, 2020)
Poultry meat is commonly marketed at refrigerated temperatures (2–5 °C). The major concern for retailers and consumers is the quality and safety of refrigerated poultry meat. During the chilling period, poultry meat undergoes too many undesirable changes due to microbial growth that leads to spoilage and economic loss. Therefore, this study was conducted to assess the effects of olive leaf extracts (OLE) used at three concentrations (0.25, 0.5, and 1%) on the sensory attributes, as well as the chemical and microbiological quality of raw poultry meat stored at 4 ± 1 °C for 15 days. The results revealed that the OLE addition reduced microbial growth successfully, and maintained the chemical quality and sensory attributes of poultry meat. Moreover, OLE extended the shelf-life of the poultry meat that held under proper refrigeration conditions up to 15 days compared to the control group, that was completely spoiled by the sixth day of storage. This study concludes that OLE could be used both as a natural antioxidant and an antimicrobial preservative for chilled poultry meat held at refrigerated temperature.